Existenzgründungen: Ein Weg zur Beschäftigungsförderung? - Friedhelm Pfeiffer (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– This article discusses from an economic point of view, both theoretically and empirically, whether firm foundation enhances employment, taking into account public regulation and promotion of firm foundation. Obviously, newly founded firms create employment. Simultaneously, however, competition on goods and factor markets destroys employment in existing firms. Despite considerable progress in empirical research, the knowledge necessary to control such market processes publicly in such a way as to enhance employment is still not available. There is not enough convincing empirical evidence that entry regulation and public promotion of firm foundation have had a positive impact on overall employment in the German economy.
Keywords: 330; Unternehmensgründung - Förderung; Existenzgründungszuschuss - Erfolgskontrolle; Beschäftigungsförderung; öffentliche Förderung; Beschäftigungseffekte; berufliche Selbständigkeit; Arbeitslose